Bringing the digestibility of prebiotics into focus: update of carbohydrate digestion models. Issue 19 (28th October 2021) - Ferreira-Lazarte, Alvaro; Moreno, F. Javier; Villamiel, Mar
Abstract: Oro-gastrointestinal digestion of dietary carbohydrates involves up to six different carbohydrases in a multistage process. Enzymes from the small intestinal brush border membrane play a major role in the digestibility of these substrates. However, to date, the inclusion of these small intestinal enzymes has been dismissed in most in vitro studies carried out, despite their importance in the degradation of carbohydrates. Several in vitro and in vivo studies have demonstrated the capability of brush border enzymes to degrade certain "non-digestible" carbohydrates to a different extent depending on their structural composition (monomeric composition, glycosidic linkage, etc.). In this sense, considering the available evidence, mucosal disaccharidases embedded in the small intestinal brush border membrane vesicles must be considered in addition to α-amylases; therefore, new approaches for the evaluation of the digestibility of carbohydrates have been recently reported. These new methods based on the utilization of the small intestinal enzymes present in the brush border membrane aim to fulfill the final and key step of the digestion of carbohydrates in the small intestine. Here, rat small intestinal extract enzymes as well as brush border membrane vesicles from pig have emerged as very reliable and useful tools to evaluate carbohydrate digestion. Thus, this review aims to go briefly through the most relevant digestion methods for carbohydrates that are currently available and to highlight the new improved methods, which include mammalian intestinal enzymes, and their current use in the evaluation of the digestibility of prebiotics.